(untitled) (Editora Impacto Científico, 2025)
The expansion of the internet and the increasing presence of children and adolescents in the digital environment have exposed this audience—still in the process of moral development—to significant risks, such as cyberbullying, the spread of fake news, and neglect of online privacy. In this context, this research aims to investigate the role of schools in the ethical and preventive education of conscious digital citizens, capable of acting responsibly and empathetically in cyberspace. The study was conducted using a qualitative approach, based on a literature review carried out through the Google Scholar platform. Works by classical authors such as Piaget (1994), Kohlberg (1984), and Dewey (1916), as well as contemporary thinkers like Castells (1999) and Floridi (2023), were analyzed, along with dissertations and articles published between 2014 and 2024. The research also considered key legal and educational frameworks governing internet use in Brazil, such as the Brazilian Civil Rights Framework for the Internet and the National Common Curricular Base (BNCC). The analysis highlighted the school’s transformative potential as a privileged space for the development of critical thinking and digital responsibility from the early stages of human development. The study concludes that the school’s preventive role, combined with public policies and family involvement, is essential for building ethical and effective digital citizenship.